Influence of green banking initiatives on green brand trust and green brand image: The mediating role of employee green behavior - Kamna Chopra, Dr Shweta Bhatia; Dr Namita Rajput, Dr. Kapil khatter (European Economic Letters (EEL), 2025)
This study explores the role of green banking initiatives and employee green behavior in building green brand image and green brand trust. The present study collected data from employees working in public- and private-sector banks. The data were collected using a non-probability convenience sampling technique, and data were analysed using the PLS algorithm along with the boot strapping method. The findings confirm that green product development, CSR, and internal processes are significant predictors of green banking initiatives. Further, green banking initiatives have a positive and significant impact on employees’ green behavior, green brand trust, and green brand image. Moreover, employee green behavior mediates between green banking initiatives, green brand trust, and green brand image. Further, the results discussed in this study can assist banking managers and policymakers in improving green brand image and trust based on green banking initiatives and employee green behavior.